Implementation Of The Keyword Mnemonic Method And Its Effectiveness To Improve Arabic Vocabulary Mastery - Ferdinand, Ilham; Yasry, Fajar Alpy (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to determine: 1. Arabic vocabulary mastery of MTs Plus Darul Hufaz Jatinangor students before implementing the mnemonic method, 2. Arabic vocabulary mastery of MTs Plus Darul Hufaz Jatinangor students before implementing the mnemonic method, 3. The effectiveness of implementing the mnemonic method with keywords on mastery Arabic Vocabulary Students MTs Plus Darul Hufaz Jatinangor. This research is experimental, using a quasi-experimental design model. This study has two variables, and the first is the independent variable, namely keyword mnemonics, and the second dependent variable is Arabic vocabulary mastery. The population of this study was all students of class VII MTs Plus Darul Hufadz Sumedang. Then a sample of class VII B was selected as the experimental class and VII A as the control class. The data collection technique is by giving a pretest, pretest, and posttest as a test. The data analysis technique uses the